Job Analysis in Improving AHASS IRZA Motor Performance - Adham, Iqbal; Pangestu, Aria Bayu (Journal of Business and Management, 2019)
Increasingly intense competition occurs in the automotive world, especially for motorcycle products, because this product is the most dominant means of land transportation owned by the people today In Indonesia. Motorcycle products from PT Astra Honda Motor (AHM) still dominated motorcycle sales in Indonesia until April 2019. The high number of sales of Honda motorcycles is supported by the big number of Astra Honda Authorized Service Station’s (AHASS) workshops which are spread throughout Indonesia. The competition will occur between fellow AHASS, therefore every AHASS must work hard to keep customers loyal just as it does to get new customers. In the last 5 years the average revenue growth of AHASS IRZA Motor was only 6.92%, which was below the target of 10%. Those issues caused because customers feel dissatisfied because they feel the process of service provided takes a long time. The cause of the length of the servants is that the employees are confused with the work they must do because the available job description is only in the form of points explain narratively.